Circulating microRNAs demonstrate limited diagnostic potential for diabetic retinopathy in the population of Kazakhstan - Aizhan Magazova; Yeldar Ashirbekov; Arman Abaildayev; Kantemir Satken; Gulzhakhan Utegenova; Ayaz Belkozhayev; Altynay Balmukhanova; Zaure Dzhumatayeva; Ainagul Beissova; Iryna Shargorodska; Aigul Balmukhanova; Kamalidin Sharipov (PeerJ)
Background Diabetic retinopathy (DR) is the most common complication of diabetes, leading to blindness. The asymptomatic onset and the existing difficulties in diagnosing warrant the search for biomarkers that can facilitate the early diagnosis of DR. The aim of this study was to evaluate the potential of plasma microRNAs (miRNAs), which have previously been shown to be involved in the pathogenesis of DR and differentially expressed in plasma/serum of patients, as biomarkers for DR in the Kazakhstani population. Materials and Methods Using quantitative RT-PCR, we compared the levels of ten candidate miRNAs in plasma among three groups: type 2 diabetes mellitus (T2DM) patients with DR (DR patients, N = 100), T2DM patients without DR (noDR patients, N = 98), and healthy controls (N = 30). Results Level of miR-423-3p was significantly reduced in DR patients compared to noDR patients (pFDR = 5.4 × 10−3). Levels of miR-423-3p and miR-221-3p were significantly reduced in DR patients compared to controls (pFDR = 5.4 × 10−3 and 0.024, respectively ), level of miR-23a-3p was significantly reduced in noDR patients compared to controls (pFDR = 0.047), levels of miR-221-3p and miR-23a-3p were significantly reduced in T2DM patients (combined group) compared to controls (pFDR = 0.047, and 0.049, respectively). Also, there were several significant differences between groups formed based on clinical-pathological characteristics, but none of these results remained significant after adjustment for multiple comparisons. Correlation analysis revealed weak associations between the levels of miR-423 and miR-221-3p and DR staging (pFDR = 1.3 × 10−3 and 0.026, respectively), and fair associations between the levels of miR-29b-3p and miR-328-3p and diabetes duration in noDR patients (pFDR = 8.8 × 10−3 and 0.016, respectively). According to receiver operating characteristic (ROC) analysis, only miR-23a-3p can be considered a potential biomarker with moderate informativeness for diagnosing proliferative DR (PDR); however, a larger sample size is needed to verify this finding. Furthermore, the small magnitude of observed changes in miRNA levels between groups significantly complicates classification. Conclusions Due to the low specificity and small magnitude of deviations from the norm, the studied miRNAs have low potential in the diagnosis of DR.